FLT3, NPM1, DNMT3a and NRAS genes mutation in acute myeloid leukaemia in HUSM - Mat Yunus, Noraini (2015)
Acute myeloid leukaemia (AML) is a rare but the most common occurrence among hematologic malignancy and associated with the greatest mortality in adults. FMS-like tyrosine kinase 3-internal tandem duplication (FLT3-ITD) and nucleophosmin 1 (NPM1) mutations are the most common genes mutation found in adult AML and have been associated with poor and good prognosis, respectively. Published data on the prevalence of FLT3-ITD and NPM1 mutations of AML adult patients in Malaysia are not available online. Thus, this study was conducted to determine the frequency of FLT3-ITD and NPM1 mutation as well as FLT3-TKD, DNMT3a, and NRAS, the types of mutations, two-years overall survival/median survival time of FLT3-ITD+/FLT3-ITD- and NPM1+/NPM1- group, and the related clinical data for mutant FLT3-ITD and NPM1 within the adult Malaysian AML patients. In this study, the genomics DNA from 54 newly diagnosed adult AML patients were retrieved from Hospital Universiti Sains Malaysia, Kelantan. Polymerase chain reaction followed by conformation sensitive gel electrophoresis (PCR-CSGE) technique was used to detect gene mutations in AML. The frequency of FLT3-ITD and NPM1 mutations were found to be 11% and 13%, respectively which were less compared to published data. With respect to sequence analysis, all of the mutant FLT3-ITD and NPM1 resulted in variety of amino acid sequences in every case. Based on the analysis, two types of mutation have been identified in FLT3 exon 14; ITD (six cases) and non-ITD (a single nucleotide deletion) (one case). Both kind of mutations would disturb the juxtamembrane domain function in FLT3 receptor, thus activate the continuous growth signal. Interestingly, a different finding was found in NPM1 mutation. Although the mutation was identified in the coding region of C-terminal domain, the mutation does not disturb the NPM nucleolar localization signal (NoLs) motif. FLT3-ITD mutation was associated with a significantly higher blast percentage (p-value = 0.008) and white blood cell count (p-value = 0.023) than the FLT3 wild type. On the other hand, NPM1 mutation were found not to associate with blast percentage and white blood cell count but occurred significantly higher in female patients (p-value = 0.038). Mutation was not detected in FLT3-TKD, NRAS, and DNMT3a genes. Two years overall survival (OS) analysis indicated no significant difference in both group, FLT3-ITD+/FLT3-ITD- (p-value = 0.660) and NPM1+/NPM1- (p-value = 0.714). Although the OS in FLT3-ITD+/FLT3-ITD- group showed not significantly difference, the median OS of AML patients with the FLT3-ITD was shorter than those with the wild type (9 versus 52 weeks, respectively). FLT3-ITD and NPM1 mutations were more prevalent in adult Malaysian AML patients compared to the other genes; FLT3-TKD, DNMT3a, and NRAS.